Single electro-optic curve for RGB colours in blue-phase liquid crystal display. Issue 6 (3rd May 2019) - Guo, Yuqiang; Li, Xiaoshuai; Mu, Qihui; Wang, Yifei; Zhang, Chi; Dou, Hu; Chu, Fan; Ma, Hongmei; Zhang, Hui; Wang, Qionghua; Sun, Yubao
ABSTRACT: The double-layer penetration electrode structure is proposed to obtain the low-operating voltage blue-phase liquid crystal display (BPLCD) with single electro-optic curve for red-green-blue (RGB) colours in every pixel, which is more suitable for the field-sequential-colour display. The different influences of electrode's parameters and driving methods on the electro-optical properties of the proposed BPLCD are investigated. The results demonstrate that the operating voltage can be reduced from 53.80 V to 23.00 V for red colour. Besides, the coincident voltage-dependent transmittance curves for RGB colours are obtained by adjusting the applied voltage of sub-electrode. Thus, RGB lights can pass through every pixel with single electro-optic curve, which is good for resolution enhancement and single gamma driving. Besides, the maximum gamma shift of the proposed BPLCD is less than 0.1099 at 60° polar angle for the red colour, and the gamma shift difference between red and blue colours is only 0.0542. If the high dielectric constant material is used as the protrusion, the operating voltage can be further decreased, which is close to that of the BPLCD with wall-shaped electrode structure. GRAPHICAL ABSTRACT: